Spectral phase-field model of deformation twinning and plastic deformation. (August 2021) - Hu, Xin; Ji, Yanzhou; Chen, Lei; Lebensohn, Ricardo A.; Chen, Long-Qing; Cui, Xiangyang
Abstract: Deformation twinning is critical to understanding and predicting the heterogenous deformation of many important material systems, e.g., hexagonal metals. In this work, we report a Fast-Fourier-Transform (FFT) based spectral phase-field method (PFM) model of deformation twinning and plasticity by directly incorporating the spectral FFT elasto-viscoplastic formulation, which allows two-way coupling between morphological evolution of deformation twinning and elastoplastic deformation. We verify the model by studying the twinning morphology evolution and plastic deformation of Mg single crystals and comparing the results with existing experimental measurements. We then apply the model to investigate heterogeneous twinning nucleation, growth and propagation behaviors, including twin-twin interactions, double twinning, and twin-grain boundary interactions. This work not only provides useful insights into the underlying deformation twinning mechanisms in hexagonal crystals but also presents an efficient PFM model of deformation twinning and plasticity which is generally applicable to modelling and predicting morphological evolution of deformation twinning and its effects on elasto-plastic responses of polycrystalline materials. Highlights: Two-way efficient coupling was developed between twinning evolution and elastoplastic deformation within the FFT scheme. The stress-strain response of Mg due to deformation twinning was reproduced. 10 1 ‾ 2 − 10 1 ‾ 2 double twinning forms upon multiple passes cross compression with stress concentration at primary twinning boundaries. Strain hardening plays a significant role in twin transmissibility across GBs when misorientation angles are high. The model can deal with deformation twinning in 3D generic polycrystals.